EXECUTION OF NON-EXECUTABLE COURT DECISIONS IN CASE NO. 757/PDT.G/2022/PN.JKT.PST - Poernomo, Achmad Ganis; Sholehuddin, Dr. M. (jfpublisher, 2024)
Judges play an important role in upholding justice as they are responsible for resolving cases and ensuring that the law is applied fairly. While their decisions are necessary to resolve cases, the fact is that they cause controversy for many parties. Judges are expected to consider law, justice, expediency, and legal certainty in making decisions. This research topic is an important and necessary study to determine the causes of Decision No. 757/Pdt.G/2022/PN.Jkt.Pst being non-executable and the legal remedies for the execution of the decision. This research is a normative juridical research using primary legal materials and secondary legal materials to obtain a comprehensive understanding. Meanwhile, this research approach uses a statutory approach, conceptual approach and case approach. The result of this research is that the judge's decision in the case between Prima Party and General Election Commission was flawed in several ways. The decision exceeded the authority of the judge, did not provide legal certainty, could have an impact on the postponement of the 2024 elections, and was ordered to be implemented immediately without following proper procedures and therefore should be considered a non-executable decision. This decision will also affect third parties, which are all legal subjects who are not parties to the civil case. Legal remedies that can be taken by the parties are to continue to take legal remedies by filing a complaint to the Supreme Court Internal Supervisory Board and submitting a report to the Judicial Commission.